The Role of Digital Catalogs in Preserving Pacitan Batik Cultural Heritage - Fera Ratyaningrum, Fera Ratyaningrum; Ika Anggun Camelia; Martadi; Djuli Djatiprambudi (Proceeding of International Joint Conference on UNESA, 2025)
Preservation of cultural heritage is key to maintaining national identity amidst globalization. Pacitan Batik, as part of a local culture rich in aesthetic and historical values, faces challenges in terms of regeneration and documentation. This study aims to identify the role of digital catalogs in preserving Pacitan batik and analyze its impact on society and the younger generation. Using a qualitative approach with a case study method in the Woro Srikandi Pacitan batik home industry, data were collected through interviews, observations, and document analysis. The results of the study indicate that digital catalogs not only function as documentation media, but also as a means of education and promotion. This catalog expands access to information about batik, increases cultural awareness, and supports learning and development of digital skills. However, limited infrastructure and digital literacy are still major obstacles. Therefore, synergy between artisans, government, educational institutions, and the community is needed to optimize the use of digital catalogs. In conclusion, digital catalogs have great potential in maintaining the sustainability of Pacitan Batik and can be a model for technology-based cultural preservation in other regions.